Text Phonopoetics - Azimjanovna, Tursunova Odina (European Journal of Life Safety and Stability (2660-9630), 2021)
The artistry of the language of a prose work is different; it cannot be approached with the criteria of poetry. The limitation of tropes in prose, about various stylistic figures, does not show the completeness of the language, since the beauty of the mystery of the language of fictional prose lies in its deeper layers. To systemize phonopoetic means of the Uzbek language, to define the theoretical foundations of phonopoetic means through poetic text analysis and revealing their aesthetic, emotional function.